THE RELATIONSHIP BETWEEN THE ROLE OF FAMILY AND THE READINESS OF FEMALE STUDENTS IN FACING MENARCHE - Venezuela, Fanny; Mita, Mita; Rahmawati, Nadia (Journal of Maternity Care and Reproductive Health, 2024)
The current trend of decreasing menarche age has caused many high-grade elementary school students to experience menarche. Currently, the age of menarche tends to get younger with an average age between 9-12 years old, which causes children to need family roles to prepare themselves to face menarche. This research aimed to determine the relationship of family role with female students’ readiness in facing menarche at Kartika XVII-3 Sungai Raya Elementary School. This research was conducted from February 28 to March 2, 2024. This research was quantitative research, with a cross-sectional approach. The sample collection technique used a questionnaire. With a sample number of 39 using the total sampling method. Data analysis using the Spearman Rank test. The age range of respondents was 9-13 years, with the highest number aged 11 years as much as 46.2%. In the criteria for parental employment, 69.2% of respondents were IRT. As many as 74.4% of children get information sources from families. Family roles 61.5% of respondents have family roles that are not good. There are 69.2% of respondents are not prepared for menarche. The results of the Spearman Rank test found that the p-value < α (0.000 ≤ 0.005) and there was a relationship between the role of family and the readiness of female students in facing menarche at Kartika XVII-3 Sungai Raya Elementary School. The information obtained by the child from the family will further affect a child's readiness to face the first menstruation. Information about menstruation is not conveyed properly and correctly, it will affect the child's readiness to face menstruation. Future researchers are expected to be able to develop more deeply the relationship between family roles and the readiness of schoolgirls to face menarche and can develop other variables that affect the unpreparedness to face menarche so that they can be used for further research.